Faktor Psikososial dari Stres Kerja Polisi: Studi Literatur Sistematis - Devy Maria Kristiani; M. Suharsono; M.Sih Setija Utami (Universitas Malahayati, 2026)
ABSTRACT Psychosocial factors of police occupational stress indicate that the mechanisms of police occupational stress tend to be complex. This is due to the nature of the work itself and its interaction with the social and psychological environment. Identifying psychosocial factors in the workplace means considering how work influences an individual's feelings, thoughts, and behaviors, thus gaining a comprehensive understanding for developing interventions for police occupational stress.To identify psychosocial factors of police occupational stress based on a systematic literature review. A Systematic Review of Literature (SRL) was conducted using the PICOC (Population, Intervention, Comparison, Outcomes, and Context) approach. The review examined 21 empirical research journals from 2019-2024, covering the psychosocial factors of police occupational stress, published in Scopus-indexed international journals, reputable international journals, international journals, and reputable national journals (Sinta). Journals were obtained from a search engine (Google Chrome) and analyzed using narrative meta-synthesis. Psychosocial factors of police work stress span personal, operational, organizational, and socio-political contexts. Gender and urban vs. rural locations are noted personal factors. Operational issues are the most frequently cited psychosocial factors. Administrative burden is the most frequently cited organizational complaint. The psychosocial factors of police work stress encompass personal, operational, organizational, and socio-political contexts. Examining gaps in psychosocial concepts and research methods is important. Keywords: Personal Stressors, Operational Stressors, Organizational Stressors, Socio-Political Contexts, Police. ABSTRAK Faktor psikososial dari stres kerja polisi memperlihatkan bahwa mekanisme terjadinya stres kerja polisi cenderung kompleks. Hal ini dikarenakan sifat pekerjaan itu sendiri dan interaksinya dengan lingkungan sosial dan psikologis juga kompleks. Mengidentifikasi faktor psikososial di tempat kerja berarti mempertimbangkan bagaimana pekerjaan akan mempengaruhi perasaan, pikiran, dan perilaku individu, sehingga dapat diperoleh pemahaman yang komprehensif untuk mengembangan intervensi stres kerja polisi.Untuk mengidentifikasi faktor psikososial dari stres kerja pada polisi berdasarkan kajian sistematis literatur. Systematic Review Literature (SRL) dilakukan dengan PICOC (Population, Intervention, Comparison, Outcomes, dan Contex). Kajian dilakukan terhadap 21 jurnal penelitian empiris dari tahun 2019-2024, mengenai faktor psikososial dari stress kerja polisi, serta dipublikasikan di jurnal internasional terindeks scopus, jurnal internasional bereputasi, jurnal internasional, dan jurnal nasional bereputasi (Sinta). Jurnal diperoleh dari search engine (google chrome), kemudian dianalisis menggunakan meta-sintesis secara naratif. Identifikasi faktor psikososial dari stres kerja polisi meliputi faktor personal, faktor operasional, organisasional, dan konteks sosial-politik. Gender dan daerah perkotaan vs pedesaan merupakan faktor personal dari psikososial stres kerja. Faktor operasional merupakan faktor psikososial yang paling banyak dikemukakan polisi. Beban administrasi merupakan faktor organisasional yang paling banyak dikeluhkan polisi. Faktor psikososial dari stres kerja polisi meliputi faktor personal, faktor operasional, organisasional, dan konteks sosial-politik. Pentingnya mengkaji lebih lanjut celah kesenjangan yang ada terkait konsep psikososial dan metode penelitian. Kata Kunci: Stressor Personal, Stressor Operasional, Stressor Organisasional, Konteks Sosial-Politik, Polisi.